ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT BELI KONSUMEN TERHADAP PRODUK FASHION ONLINE MELALUI JEJARING SOSIAL INSTAGRAM - Nurwibowo, Rifqi Wildan; Indriani, Farida (Faculty of Economics and Business Diponegoro University, 2017)
E-commerce success, especially in the business-to-consumer area, is determined in part by whether consumers trust sellers and products they cannot see or touch, and electronic systems with which they have no previous experience. This research describes a theoretical model for investigating the influence of ease of use, risk and trust towards the customer’s purchase intention of online fashion using Instagram as media. The sampling is non-probability with snowball technique. Samples were collected from 100 respondents who have instagram account and following at least one online fashion shops account. Analysis method used here is regression which includes validity test, reliability test, t-test, f-test and determination test.The result showed that ease of use, risk and trust has significant influence towards the customer’s purchase intention. This research finds that trust is a major positive determinant of customer’s purchase intention which.